Development of Quran-based curriculum on religious materials at madrasah ibtidaiyah - Rofiatul Hosna; Egara Dinnul Iza; Ahmad Wifaqi Shiddiqi; Anjir Faghnawy Achmada; Daud Daud (Inovasi Kurikulum, 2025)
This research focuses on the formulation of a Qur'an-based curriculum for developing students' interest in learning religious materials at Madrasah Ibtidaiyah An-Nur Pamekasan. The purpose of this study is to describe and analyze the formulation, design, implementation, and evaluation of the development of a Qur'an-based curriculum in Madrasah Ibtidaiyah An-Nur Pamekasan. This study employs a phenomenological qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. Data analysis was conducted in an interactive, analytical, and descriptive manner. The study's results show that the formulation of a Qur'an-based curriculum at Madrasah Ibtidaiyah An-Nur Pamekasan is a response to the needs of students and their environment. The development design contains the methods offered by the madrasah for the Qur'an-based curriculum development program. The implementation stage of its development has three important elements: 1) Implementing elements, curriculum developers, madrasah heads, and other madrasah components. 2) Based on the Qur'an, which is packaged in the Qur'anic learning supplement program, 3) The target group students. The evaluation of its development encompasses several stages and procedures, including the evaluation of the Qur'an-based curriculum, Tahfidz al-Qur'an, and Fahmu al-Qur'an, as well as reference to the indicators of the three goals.   Abstrak Penelitian ini berfokus pada formulasi pengembangan kurikulum berbasis al-Qur’an dalam meningkatkan minat belajar siswa pada materi keagamaan di Madrasah Ibtidaiyah An-Nur Pamekasan. Tujuan penelitian ini adalah mendeskripsikan dan menganalisis formulasi Madrasah Ibtidaiyah An-Nur Pamekasan, desain, implementasi, dan evaluasi pengembangan kurikulum berbasis al-Qur’an. Penelitian ini menggunakan pendekatan kualitatif fenomenologis dengan menggunakan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan secara deskriptif analitis interaktif. Hasil penelitian menunjukkan bahwa formulasi pengembangan kurikulum berbasis al-Qur’an di Madrasah Ibtidaiyah An-Nur Pamekasan merupakan respons terhadap kebutuhan peserta didik dan lingkungannya. Desain pengembangannya berisi tentang metode yang ditawarkan oleh madrasah untuk program pengembangan kurikulum berbasis al-Qur’an. Tahap implementasi pengembangannya memiliki 3 unsur penting: 1) Unsur pelaksana, pengembang kurikulum, kepala madrasah dan komponen madrasah yang lain. 2) Berbasis al-Qur’an yang dikemas dalam program penambahan pembelajaran al-Qur’an, 3) Target group sasaran peserta didik. Evaluasi pengembangannya mencakup beberapa tahapan dan prosedur, diantaranya: Evaluasi pengembangan kurikulum berbasis al-Qur’an, Tahfidz al-Qur’an dan Fahmu al-Qur’an, serta merujuk pada indikator dari ketiga tujuan tersebut. Kata Kunci: Al-Qur'an; materi keagamaan; pengembangan kurikulum